TRANSFORMATIONAL LEADERSHIP OF THE PRINCIPAL IN THE IMPLEMENTATION OF THE PROFESSIONAL LEARNING COMMUNITY (PLC) - Lagarense, Fabiola; Purwanto, Nurtanio Agus; Hemamalini, Hemamalini (Universitas Labuhanbatu, 2025)
Purpose - This research aims to determine and describe the transformational leadership of school principals in implementation Professional Learning Community (PLC) at the Elementary School level.Methodology - The method used in this research is descriptive qualitative. This research was conducted at SD Negeri Kyai Mojo and SD Negeri Vidya Qasana. The subjects of this research are school principals and teachers. Data collection techniques use observation, interviews and document study. Data were analyzed by referring to Miles & Huberman's theory, namely data collection, data condensation, data presentation, and drawing conclusions.Findings - The results in this study show that: (1) Planning Professional Learning Community (PLC) at SD Negeri Kyai Mojo, namely: formulating a clear vision and goals, carrying out needs analysis, organizing strategic resources (forming a learning community team